2010
DOI: 10.1016/j.bbmt.2010.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea during the Conditioning Regimen Is Correlated with the Occurrence of Severe Acute Graft-versus-Host Disease through Systemic Release of Inflammatory Cytokines

Abstract: Graft-versus-host disease (GVHD) is a major obstacle to the success of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Although many indicators have been used to predict GVHD, the prediction of GVHD remains very difficult. Determining how to predict the occurrence of acute GVHD (aGVHD) as exactly as possible has been a huge challenge so far. Systemic release of inflammatory cytokines during the conditioning regimen and early-phase post-HSCT plays a crucial role in the generation of aGVHD; addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 20 publications
0
28
0
3
Order By: Relevance
“…Another limitation of our study is that data were unavailable on diarrhea related to conditioning, a GVHD risk factor independent of mucositis [4, 5]. In addition, our study was uninformative about hyperacute GVHD, because our eligibility criteria excluded from the cohort those patients who developed GVHD before Day 11 after allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our study is that data were unavailable on diarrhea related to conditioning, a GVHD risk factor independent of mucositis [4, 5]. In addition, our study was uninformative about hyperacute GVHD, because our eligibility criteria excluded from the cohort those patients who developed GVHD before Day 11 after allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…11 Liu et al showed that a mean volume of conditioning-related diarrhea for Days −3 to 0 larger than 7.94 mL/kg was an independent risk factor for the development of grade II-IV aGVHD. 12 Johansson et al showed that higher intestinal absorption of 51 Cr-EDTA in the first two weeks following transplant predicted the development of grade II-IV aGvHD. 13 We hypothesize that the early post-transplant period, when intestinal barrier damage is maximal and before aGvHD has developed, is a critical window during which high-risk features on abdominopelvic imaging are associated with the risk of subsequent aGvHD development.…”
Section: To the Editormentioning
confidence: 99%
“…It is worthy to test whether the manipulation of intestinal microbiome is able to reduce the risk of acute GVHD. Considering the considerable difference of conditioning regimen or GVHD prophylaxis in the regimen-related toxicity of oral mucosa and gastrointestinal tract, importance of gut bacterial manipulation might be more important in patients with a myeloablative conditioning regimen than those with a reduced-intensity conditioning regimen, or in patients with short-term methotrexate than those with mycophenolate mofetil (3540). …”
Section: Gut Bacteria and Gvhdmentioning
confidence: 99%